Leadership Style at the Contemporary Pesantren Al-Hilmu Prigen Pasuruan - Anasro, Anasro; El-Yunusi, Muhammad Yusron Maulana (Lembaga Pengembangan Pesantren dan Diniyah Provinsi Jawa Timur, 2024)
Leadership style in Islamic boarding schools is often rooted in the charisma and independence of a leader known as Kiai, resulting in a predominantly authoritarian leadership style. This research aims to analyze the leadership style within Islamic boarding school institutions. The subject of this research is the Contemporary Islamic Boarding School Al-Hilmu in Prigen, Pasuruan. The research method employed is qualitative descriptive, focusing on 1) the tendencies of leadership styles in boarding schools and several aspects contributing to these styles. Data collection methods include observation, interviews, and documentation, while data analysis involves data reduction, data display, and conclusion drawing. The research findings conclude that 1) Based on the study of power source utilization, leadership behavior, and decision-making, it is concluded that the leadership style in the contemporary Islamic boarding school Al-Hilmu Prigen Pasuruan predominantly emphasizes a democratic leadership style. 2) Several factors contributing directly to the democratic leadership style in Al-Hilmu Prigen Pasuruan include a) vision and mission factors, b) characteristics and strengths of the boarding school, and c) educational levels (ability factor).